INTERACTION BETWEEN GROUNDWATER RESOURCES, AGRICULTURAL PRODUCTION AND WATER EXPLOITATION INFRASTRUCTURE IN SREPOK RIVER BASIN (VIETNAM) - MK17 Project Team (CGIAR Challenge Program on Water and Food, 2013)
In Vietnamese: In the past decades, the exploitation and use of water resources (surface and groundwater) and the prevention and control of water-caused disasters in the Srepok River Basin have gained important achievements, contributing greatly to socio-economic development of the basin. However, we have not been fully aware in a long time of the meaning and importance of sustainable water resources exploitation and use for socio-economic development, life, health and environment, we have not paid enough attention to the management and protection as well as planning of water resources utilization. This led to degradation of water resources in both quantity and quality; water pollution, water shortage, water scarcity occurred in many places and tend to increase in recent years.